Factors affecting morbidity and mortality on-farm and on-station in the Ethiopian highland sheep - Bekele, T.; Wolde-Ab, T.; Lahlou-Kassi, A.; Sherington, J. (Elsevier, 1992)
Discusses factors affecting morbidity and mortality of the Ethiopian highland sheep both on-farm and on-station at Debre Berhan between 1989 and 1990. Primary causes of infections origin resulted in high proportional morbidity (88.4 percent on-farm) and mortality (72.9 percent on-farm and 71.8 percent on-station) rates. Nutritional and management factors were also responsible for mortalities of lambs. Ectoparasites, nasal nyiasis, health management factors, gastro-intestinal parasites, pneumonia, fasciolasis, and enteritis also were found to be causes of morbidity and mortality. Suggests a proper health management intervention involving vaccination, strategic anthelmintic treatment and feeding management to alleviate the major health problems.